Cancer Screening Knowledge and Behavior in a Multi-Ethnic Asian Population: The Singapore Community Health Study - Chan, Tyson Kin-Chung; Tan, Linda Wei Lin; van Dam, Rob M.; Seow, Wei Jie (Frontiers in Oncology, 2021)
Background: Cancer has become the leading cause of mortality in Singapore and among other Asian populations worldwide. Despite the presence of National Cancer Screening programmes in Singapore, less than half of the population has had timely screening according to guidelines. The underlying factors of poor cancer screening rates and health outcomes among Asian ethnic groups remain poorly understood. We therefore examined cancer screening participation rates and screening behaviour in a multi-ethnic Singapore population. Methods: We collected data from 7,125 respondents of the 2015-2016 Singapore Community Health Study. Factors associated with cervical, breast, and colorectal cancer screening were evaluated using modified Poisson regression. Adjusted prevalence ratios were computed with 95% confidence intervals after adjusting for confounders. Results: The respondents’ mean age was 57.7±10.9 years, 58.9% were female and were predominately Chinese (73.0%), followed by Malay (14.2%) and Indian (10.9%). Less than half of the respondents in the recommended age groups had undergone cancer screening (cervical, 43%; breast, 35.1%; colorectal, 27.3%). Malay respondents were significantly less likely to screen as recommended for cervical (aPR=0.75, CI=0.65-0.86, p<0.001), breast (aPR=0.83, CI=0.68-0.99, p=0.045) and colorectal cancer (aPR=0.55, CI=0.44-0.68, p<0.001), as compared to Chinese respondents. Respondents who had obtained lower secondary level education were 42% more likely to screen for cervical cancer (aPR=1.42, CI=1.23-1.64, p<0.001), and 22% more likely to screen for breast cancer (aPR=1.22, CI=1.02-1.46, p=0.032), compared to those with primary level education and below. Respondents with a household income ≥S$10,000/month were 71% more likely to screen for breast cancer (aPR=1.71, CI=1.37-2.13, p<0.001), as compared with <$2,000/month. Conclusions: Ethnicity and socio-economic status were significantly associated with lower uptake of cancer screening tests in Singapore. To improve the screening uptake among disadvantaged groups, a multi-faceted approach is needed that addresses the barriers to screening such as the adequacy of subsidy schemes and ethnic differences.